Unpacking the dangers of super absorbent polymer water beads: an in vitro analysis - Hachem, Jack J.; Monagas, Javier; Banerjee, Ankona; Noel, Robert A. (Frontiers in Pediatrics, 2025)
ObjectivesThis study aims to investigate the risk of pediatric bowel obstruction from various types of super absorbent polymer (SAP) beads in different liquid media, explore treatment options, and develop a clinical decision-making algorithm for healthcare providers.MethodsThree experiments were conducted involving the measurement of SAP beads' expansion in different liquid media. The first experiment examined the expansion of beads in tap water, gastric fluid, and small intestine fluid. The second compared the expansion of beads from six manufacturers in water. The third tested the effect of varying concentrations of Polyethylene Glycol 3350 on bead expansion.ResultsThe study found that SAP beads reached their largest size in water, with significant size-dependent and solution-specific effects on their expansion. Large beads had a β of 12.67 (95% CI: 10.25–15.1; p < 0.001) compared to small beads. Gastric acid reduced expansion with a β of −7.01 (95% CI: −9.67 to 4.35; p < 0.001) and alkaline solution with a β of −3.88 (95% CI: −6.54 to 1.23; p = 0.002) compared to water. Treatment solutions containing high concentrations of polyethylene glycol (PEG) 3350 effectively reduced the size of the beads (p < 0.001).ConclusionsThis research highlights the importance of understanding the characteristics and risks associated with SAP beads to mitigate the dangers they pose to pediatric populations. Our findings underscore the need for standardized management of SAP bead ingestion, which could improve patient outcomes while reducing unnecessary diagnostic and therapeutic interventions. Further research and clinical validation of these strategies in vivo are essential to develop safe and efficient protocols for managing SAP bead ingestions